Muslim in Malaysia Understanding in Regards to the Concept of Compatibility (Kafa’ah) in Islamic Marriage - Mohd Kusrin, Zuliza; Yusof, Wafaa’; Ismail, Nor Faizah; Che Abdul Rahim, Norsyamlina; Hibaoui, Abderrahmane (El-Usrah: Jurnal Hukum Keluarga, 2024)
Islam provide guidelines for choosing spouse based on compatibility (kafa’ah or sekufu). The criteria include equality in religion, wealth, lineage, beauty, health, and social status. However, divorce cases indicate that it occurs due to lack of compatibility between the spouse. This study discusses the concept of compatibility in Islam and respondent’s understanding on it. It involved 355 Muslim respondents, in Malaysia. A set of questionnaires was distributed, then the data were analysed descriptively. The result recorded a high agreement percentage on the respondents' understanding of kafa'ah in religion, wealth, lineage, ethnicity, beauty, health, social. A high agreement percentage also resulted in their understanding of compatibility as guidance for choosing spouse and guardian (wali)’s authority in compatibility (kafa'ah). As a conclusison, the respondens’ understanding on the concept of compatibility (kafa’ah) is high and it is hope that it will become a guidance for them and community while choosing their future spouses